Implementation Of Individual Guidance Through Whatsapp Group To Increase Achievement And Learning Motivation Of Students Of Class VII SMP Negeri 3 Ngaglik Sleman 2020/2021 - Suratmi Suratmi (International Journal of Chemistry Education Research, 2021)
This study aims to increase the learning motivation of seventh-grade students of SMP Negeri 3 Ngaglik Sleman through "WhatsApp Group" in individual guidance. The population in this study was 369 students. The sample in this study was class VII SMP Negeri 3 Ngaglik Sleman totaling 128 which was divided into 3. The research method used in this study was Action research Guidance Counseling with the model developed by Kemmis and Mc. Taggart goes through four stages, namely planning, action, observation, and reflection. The research flow is carried out in two cycles. The results showed that the application of individual guidance through WhatsApp Group to the learning outcomes of Class VII students of SMP Negeri Ngaglik Sleman could increase. The average student evaluation results have exceeded the minimum value for each subject. As for the results after the students carried out mentoring activities for 3 cycles, as many as 5 students were in the very good category, and as many as 25 students were in a good category, and in the sufficient category as many as 2 students. Overall, the development of learning outcomes before being given action (pre-action) and after being given action for 3 cycles increased by 93.75%. Based on the results of the study showed that as much as 85% in the process of applying individual guidance through "WhatsApp group" on learning motivation can be used as an alternative in an effort to improve the process and learning outcomes of students.